The Vengeance of Vertigo: Aphasia and Abjection in the Political Trials of Black Insurgents - Wilderson, Frank B., III (InTensions, 2011)
The guerilla war that the Black Liberation Army waged against the United States in the late 1960s, 1970s, and early 1980s was part of a multifaceted struggle to redress Black dispossession which has been waged since the first Africans landed in the “New” World.ii But the political trials of BLA soldiers marked an unprecedented moment in the history of that struggle; a moment when it became de rigueur for revolutionaries to refuse the role of defendant and assume (while still in custody and often handcuffed) the role of prosecutor and judge—with the public gallery as jury. This shift comprised an unparalleled inversion of jurisprudential casting in which the court itself (and by extension the U.S. government) became defendants. Assata Shakur recalls how brothers and sisters came to her trial every day to “watch the circus.” Her narrative paints a vibrant picture of an intra-mural conversation between Black folks from all walks of life, for whom the court and the trials functioned much like backwoods churches did during slavery. A courtroom of people who joined the defendants in their refusal to rise when the judge came in; folks giving each other the Black Power salute in full view of the U.S. Marshals; Black Muslim men and women spreading their prayer rugs in the corridors of the court and praying to Allah; Black parents explaining the underlying racism of the American legal system to their children. As the judge entered the courtroom, one such well-educated child looked up and said, “Mommy, is that the fascist pig?” to the laughter and applause of the gallery (Assata 212).